Does codetermination affect the composition of variable versus fixed parts of executive compensation? - Dyballa, Katharina; Kraft, Kornelius (Mannheim, 2015)
"Contrary to previous literature we hypothesize that interests of labor may well – like that of shareholders – aim at securing the long-run survival of the firm. Consequently, employee representatives on the supervisory board could well have an interest in increasing incentive-based compensation to avoid excessive risk taking and short-run orientated decisions. We compile unique panel data on executive compensation over the periods 2006 to 2011 for 405 listed companies and use a Hausman-Taylor approach to estimate the effect of codetermination on the compensation design. Finally, codetermination has a significantly positive effect on performance-based components of compensation, which supports our hypothesis."